PENGARUH KINERJA KEUANGAN TERHADAP HARGA SAHAM (PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK) PERIODE 2019-2021 - Any Fitriya Mulyani; Syafrudin Arif Marah Manunggal (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2023)
The purpose of this study was to test and analyze the effect of the Capital Adequency Ratio (CAR), Loan to Deposit Ratio (LDR), Return on Assets (ROA) and Debt to Equity Ratio (DER)  on  stock  prices.  The  objects  of  this  research  are  banking  companies  listed  on  the Indonesia  Stock  Exchange  in  2019-2021.  The  population  in  this  study  were  all  banking companies listed on the Indonesia Stock Exchange, namely 106 banks.  Determination of the sample using purposive sampling method, with a total sample of 25  banking companies that have certain criteria.  The method used is panel data regression analysis  with the help of the E-Views  12  application.  The  results  of  this  study  partially  indicate  that  Return  on  Assets (ROA)  loan  to  Deposit  ratio  (LDR)  and  Capital  adequacy  ratio  (CAR)  has  a  significant positive effect on stock prices. Meanwhile,  Debt to Equity  Ratio  (DER)  have no significant effect on stock prices on the Indonesia Stock Exchange (IDX) for the 2019-2021 period